Sustained HSP25 Expression Induces Clasmatodendrosis via ER Stress in the Rat Hippocampus - Kim, Ji-Eun; Hyun, Hye-Won; Min, Su-Ji; Kang, Tae-Cheon (Frontiers in Cellular Neuroscience, 2017)
Heat shock protein (HSP) 25 (murine/rodent 25 kDa, human 27 kDa) is one of the major astroglial HSP families, which has a potent anti-apoptotic factor contributing to a higher resistance of astrocytes to the stressful condition. However, impaired removals of HSP25 decrease astroglial viability. In the present study, we investigated whether HSP25 is involved in astroglial apoptosis or clasmatodendrosis (autophagic astroglial death) in the rat hippocampus induced by status epilepticus (SE). Following SE, HSP25 expression was transiently increased in astrocytes within the dentate gyrus, while it was sustained in CA1 astrocytes until 4 weeks after SE. HSP25 knockdown exacerbated SE-induced apoptotic astroglial degeneration, but mitigated clasmatodendrosis accompanied by abrogation of endoplasmic reticulum (ER) stress without changed seizure susceptibility or severity. These findings suggest that sustained HSP25 induction itself may resulted in clasmatodendrosis via prolonged ER stress. To the best of our knowledge, the present study demonstrates for the first time the double-edge properties of HSP25 in astroglial death induced by SE.